Acute exercise increases syndecan-1 and -4 serum concentrations - Lee, Sindre; Kolset, Svein O.; Birkeland, Kåre I.; Drevon, Christian A.; Reine, Trine M. (Glycoconjugate journal, 2019)
The effects of acute and long-term exercise on syndecans and the relationship to insulin sensitivity are not fully explored. We aimed to examine the effects of acute and 12 weeks of exercise on (1) serum levels of syndecan-1 and -4, (2) gene expression related to syndecan synthesis and modification in skeletal muscle and adipose tissue, and (3) the relationship to insulin sensitivity. Sedentary men with ( n = 13) or without (n = 13) dysglycemia underwent two 45 min acute bicycle tests interspersed by 12 weeks of exercise intervention. Euglycemic hyperinsulinemic clamp and mRNA-sequencing of skeletal muscle and adipose tissue biopsies were performed before and after intervention. Serum syndecan-1 and -4 levels were quantified before, immediately after and 2 h after bicycling. Syndecan-1 and -4 serum concentrations increased in response to acute physical exercise. Baseline syndecan-4 but not syndecan-1 concentrations were higher in dysglycemic compared to normoglycemic men, and correlated to change in insulin sensitivity, but did not change during the 12 weeks exercise intervention. Only syndecan-4 was expressed in skeletal muscle and adipose tissue. Adipose tissue mRNA levels of transcripts affecting syndecan structure and shedding were upregulated in dysglycemia, and muscle mRNA responded to long-term physical activity. The increase in serum syndecan-1 and -4 due to acute exercise suggest increased syndecan shedding and disruption of glycocalyx in response to increased blood flow. The higher syndecan-4 baseline serum levels in dysglycemia, association to insulin sensitivity, and changes in mRNA transcripts may suggest syndecan-4 involvement in muscle and adipose tissue response to exercise.